2014
DOI: 10.3390/ijms15021927
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Th22 Cells Correlated with Th17 Cells in Peripheral Blood of Patients with Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is a hematological tumor in which progress T helper (Th) subsets including Th22, Th17, and Th1 cells play a pivotal role. However, the role of T helper (Th) subsets in the immune pathogenesis of AML remains unclear. Here, we investigated frequencies of Th22, Th17, pure Th17, and Th1 cells in the peripheral blood (PB) of AML patients. We demonstrated that Th22, Th17, and pure Th17 in newly-diagnosed (ND) and non-complete remission (Non-CR) AML patients and plasma IL-22 in ND AML pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…IL-22, as the main effector cytokine of Th22, belongs to the IL-10 cytokine family [ 15 ]. Recent studies have implicated the role of Th22 and IL-22 in the pathogenesis of a variety of solid tumors and a limited number of hematological malignancies including AML [ 16 ], MDS [ 17 ] and ALL [ 18 ]. No data has been reported regarding the role of Th22 cells and IL-22 in the pathogenesis of CML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-22, as the main effector cytokine of Th22, belongs to the IL-10 cytokine family [ 15 ]. Recent studies have implicated the role of Th22 and IL-22 in the pathogenesis of a variety of solid tumors and a limited number of hematological malignancies including AML [ 16 ], MDS [ 17 ] and ALL [ 18 ]. No data has been reported regarding the role of Th22 cells and IL-22 in the pathogenesis of CML.…”
Section: Discussionmentioning
confidence: 99%
“…The current data regarding the role of Th17 cells in pathogenesis of cancer are scarce and controversial [ 27 ]. There are several researches about the roles of Th17 in hematological malignancies including multiple myeloma [ 28 ] and CLL [ 29 ], AML [ 16 , 30 ], and non-Hodgkin lymphoma [ 31 ]. It has been reported that serum levels of IL-17 are increased in multiple myeloma patients and are correlated with disease prognosis, which suggested IL-17 as tumor-promoting factor in multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that Th22 cells and IL-22 may have a role in acute lymphoblastic leukemia, acute myeloid leukemia, and myelodysplastic syndromes [181]. High IL-22 concentrations and the elevated expression of CD38 may be implicated in the synergetic stimulation of genes involved in proliferation and programmed cell death.…”
Section: Effects Of Cytokines On the Onset Progression And Complicamentioning
confidence: 98%
“…On the other hand, the activation of RTKs by the c-Cbl RING finger mutation is associated with the up-regulation of many transcription factors (including Id1, Hoxb5, Rorc and Meis1) and down-regulation of many suppressor genes (including JunB, EgR1 and GATA1) [14]. The majority of these genes are involved in regulating hematopoiesis, and perturbations within these are commonly found in AML [34][35][36][37][38][39][40]. Therefore, by combining the FLT3-ITD and c-Cbl RING finger mutations a potent transcriptional environment is likely to be formed that drives the development of myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%